1996
DOI: 10.1038/379540a0
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationships for resetting of human circadian clock by light

Abstract: Since the first report in unicells, studies across diverse species have demonstrated that light is a powerful synchronizer which resets, in an intensity-dependent manner, endogenous circadian pacemakers. Although it is recognized that bright light (approximately 7,000 to 13,000 lux) is an effective circadian synchronizer in humans, it is widely believed that the human circadian pacemaker is insensitive to ordinary indoor illumination (approximately 50-300 lux). It has been proposed that the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
306
0
8

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(331 citation statements)
references
References 20 publications
17
306
0
8
Order By: Relevance
“…Also, there is a conceptual difficulty arising from recent findings on the influence of light on the circadian system. Boivin et al (1996) showed that even with the relatively dim light levels used in the present study, the imposed light/dark cycle may exert a direct influence on the ECP. This could lead to relative coordina- tion between the two rhythmic processes, resulting in a loss of stationarity in the tau rhythm and thus a loss in a true balancing of tau with respect to T (Klerman et al, 1996).…”
Section: Discussionmentioning
confidence: 57%
“…Also, there is a conceptual difficulty arising from recent findings on the influence of light on the circadian system. Boivin et al (1996) showed that even with the relatively dim light levels used in the present study, the imposed light/dark cycle may exert a direct influence on the ECP. This could lead to relative coordina- tion between the two rhythmic processes, resulting in a loss of stationarity in the tau rhythm and thus a loss in a true balancing of tau with respect to T (Klerman et al, 1996).…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, it was only the duration of time spent outside – not the intensity of light – that was found to influence MSF sc in our study except for subjects in Auckland. Although the intensity of light has been shown to impact on the entraining properties of light pulses under experimental conditions (Boivin et al 1996; Zeitzer et al 2005; Duffy and Czeisler 2009), a saturation effect on shifting the phase of the melatonin rhythm has been reported above approximately 1000 lux (Zeitzer et al 2000), equivalent to approximately 7.9 W/m 2 (based on the approximation that 1 lux = 0.0079 W/m 2 for solar irradiance). Considering the lowest average light intensity reported in this study was 19.43 W/m 2 , and therefore well above saturation intensities, it is perhaps unsurprising that no effect of light intensity emerged.…”
Section: Discussionmentioning
confidence: 99%
“…53 Another possible mechanism for the detrimental effect of electronics use on sleep is that the light produced by electronic devices may disrupt circadian rhythms by suppressing melatonin, resulting in the inability to fall asleep at a reasonable time. 40 Recent studies have demonstrated that exposure to relatively low-intensity light can alter circadian rhythms 54,55 and suppress nocturnal melatonin secretion. 56 Finally, media use may cause increased sleep-disrupting mental, emotional, and physiologic arousal.…”
Section: Electronic Media and Sleepmentioning
confidence: 99%